Value of 18F-FDG PET/CT and MRI in diagnosing primary endometrial small cell carcinoma - Wan, Qi; Jiao, Qian; Li, Xinchun; Zhou, Jiaxuan; Zou, Qiao; Deng, Yingshi (Chinese Journal of Cancer Research; Vol 26, No 5 (October 31, 2014): Chinese Journal of Cancer Research, 2014)
Primary small cell carcinoma (SCC) is a group of aggressive neoplasms that mainly arise from the lung and digestive tract. Endometrial small cell carcinoma (ESCC) is extremely rare. To our knowledge, less than 90 cases have been reported, and most of these reports were dedicated to describing the clinicopathologic or immunochemical features of ESCC. Herein, we present a new case of ESCC involving a 51-year-old woman and mainly focus on the magnetic resonance imaging (MRI) and positron emission tomography/computed tomography (PET/CT) findings. MRI showed that the uterus was significantly enlarged (11.6 cm × 11.1 cm × 14.4 cm), and a giant irregular mass (7.5 cm × 8.4 cm × 8.5 cm) was observed in the uterine cavity. The lesion demonstrated an extremely low apparent diffusion coefficient (ADC) value [(0.553±0.088)×10–3 mm2/s] and a high FDG uptake value (22.7). Multiple metastatic lymph nodes (LNs) were identified at different positions, with diameters ranging from 0.3 to 2.8 cm and a maximum standardized uptake value (SUVmax) ranging from 6.9 to 19.3.